(untitled) (Bangladesh Journal of Urology, 2020)
Objective: To compare the treatment outcome of Silodosin alone and Silodosin plusTadalafil as a medical expulsive therapy (MET) of lower ureteric stone in south-westernpart of Bangladesh. Methodology: The study was conducted in a tertiary hospital in Khulna, over a periodof 12 months (January 2019 to December 2019). Out of 108 patients, 100 meet theinclusion criteria who were purposively assigned into 2 groups. 48 patients included inSilodosin alone group and 52 in Silodosin plus Tadalafil group. Result: There was a significant higher stone expulsion rate in Silodosin plus Tadalafilthan Silodosin alone which was 88.46% vs75% respectively (P value 0.02). The meanstone expulsion time of Silodosin alone was14.33 (±3.1) days and Silodosin plus Tadalafilwas 11.48(±2.3) days (P value 0.001). The episodes of pain in Silodosin alone were0.7(±0.06) and 0.6(±0.2) in Silodosin plus Tadalafil group that was statisticallysignificant. Conclusion: The present study concludes that Silodosin plus tadalafil combinationtherapy significantly increases ureteric stone expulsion rate and decreases the expulsiontime and pain episodes than treatment with silodosin alone. Bangladesh Journal of Urology, Vol. 23, No. 1, January 2020 p.67-71